STUDENTS UNDERSTANDING OF SAVINGS PRODUCTS AND SERVICE QUALITY OF BANK TOWARDS THE SAVING INTEREST IN ISLAMIC BANK religiosity as moderating variable (Studies of the student of Islamic Banking Department UIN Ar-Raniry in 2015 Entrance Year) - Lianda Lianda; Israk Ahmadsyah; Evy Iskandar (LPPM Universitas Malikussaleh, 2018)
The aim of this study is to see the impact of student understanding of the bank's products and services of Islamic banks on the interest of saving by adding religiosity as a moderating variable. The study uses purposive sampling to select 70 respondents. The study employs the MRA (Moderated Regression Analysis) to analyze the data. The results showed that the students' understanding of savings products have a significant effect on the interests of saving. While the quality of service has no significant effect on the interest of saving. Moderating variables or religiosity is associated with a student's understanding has a significant effect of savings products. Next, religiosity is associated with the quality of bank services also have a significant effect.